ATMPH 2019
DOI: 10.36295/asro.2019.221158
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Okra Fruit (Abelmoschus Esculentus) on Fasting Blood Sugar and Total Cholesterol Level in Type 2 Diabetes Mellitus

Abstract: Background:Diabetes Mellitus is a metabolic disease characterized by hyperglycemia that occurs due to abnormal insulin secretion, insulin action or both. Complex disorders occur in type 2 Diabetes Mellitus, involving various degrees of decreased beta-cell function, peripheral insulin resistance, and abnormal liver glucose metabolism. Okra (Abelmoschus esculentus) is a plant that has an antidiabetic effect because of its efficiency in improving blood sugar control and lipid profile.Objectives:To evaluate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 6 publications
1
20
1
Order By: Relevance
“…Interestingly, this was accompanied by evidence of no heterogeneity (I 2 = 0%) (Figure 4). Thus, this leads us to conclude that heterogeneity in this meta-analysis was due to studies with low quality (ADAP et al, 2019;Haryati and Rahmawati, 2019;Khodija et al, 2020).…”
Section: Subgroup Analysis Of Okra Treatment On Fbgmentioning
confidence: 82%
See 2 more Smart Citations
“…Interestingly, this was accompanied by evidence of no heterogeneity (I 2 = 0%) (Figure 4). Thus, this leads us to conclude that heterogeneity in this meta-analysis was due to studies with low quality (ADAP et al, 2019;Haryati and Rahmawati, 2019;Khodija et al, 2020).…”
Section: Subgroup Analysis Of Okra Treatment On Fbgmentioning
confidence: 82%
“…For the incomplete outcome data domain, all studies were considered a low-risk bias; for example, five (Labadnoy et al, 2017;Sarbini et al, 2019;Ziaee et al, 2019;Moradi et al, 2020;Saatchi et al, 2022) reported the number of patients who did not complete the treatment regimen due to unwillingness to continue with the study or loss of follow-up. In contrast, the other three studies (ADAP et al, 2019;Haryati and Rahmawati, 2019;Khodija et al, 2020) did not have any loss of patients throughout the study. In terms of the selective reporting domain, all studies (Labadnoy et al, 2017;ADAP et al, 2019;Haryati and Rahmawati, 2019;Sarbini et al, 2019;Ziaee et al, 2019;Khodija et al, 2020;Moradi et al, 2020;Saatchi et al, 2022) did not have a protocol published.…”
Section: The Risk Of Bias and Quality Assessmentmentioning
confidence: 86%
See 1 more Smart Citation
“…Nearly 15% of the vegetable species had clinically proven antidiabetic properties. Most investigations were conducted on Abelmoschus esculentus, Anethum graveolens, and Musa × paradisiaca (Haryati et al, 2019;Moradi et al, 2020;Islas et al, 2005;Haidari et al, 2020;Mobasseri et al, 2014;Rao et al, 2021;Nedic et al, 2012;Chaiyasit et al, 2009;Mahmoodpoor et al, 2018;Katare et al, 2013;Evans et al, 2014;Lintas et al, 1995;Edo et al, 2011).…”
Section: Vegetable Species Had Clinical Antidiabetic Scientific Proofmentioning
confidence: 99%
“…The tender immature pods of okra are considered an affordable source of carbohydrates, proteins, fibers, vitamins, and minerals. Okra has several health benefits such as reducing blood cholesterol, promoting skin health, and stabilizing blood sugar level (Gemede et al, 2014;Haryati, 2019;Ardestani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%